Novle layered boron nitride nanosheets/cellulose nanofibers/epoxy composite with high thermal conductivity. (February 2022) - Da, Yunsheng; He, Jing; Qu, Qiqi; Zhu, Menghan; Wang, Hua; Liu, Yanyan
Studies have shown that the construction of a three-dimensional interconnected filler network is an effective method to improve the thermal conductivity of the through-plane under a lower filler load. However, huge challenges still exist in building a long-range layered filler network and reducing the thermal resistance resulting from contact between fillers and matrix. In this work, boron nitride nanosheets (BNNSs) were proposed to be connected with modified cellulose nanofibers (CNFs) to obtain a long-range layered structure filler skeleton by bidirectional freezing orientation. Then epoxy resin was dipped under vacuum condition to prepare composite with thermal conductivity up to 1.43 W/mK in through-plane when filler content is 4.3 vol%, and the composite had low thermal expansion coefficient of 64.1 ppm/°C and excellent volume resistivity up to 3.7 × 10 12  Ω cm at the same time.